Future Trends in Human Resource Management (HRM) and Marketing: A Case Study in the Tourism Sector - Syamsuddin, Asmawaty; Gumilar, Gugung (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The hospitality industry is very competitive including Renjana Beach House which has challenges from the menu and hotel marketing on social media. This study examines human resource management and marketing strategies at Renjana Beach House in Bira, Bulukumba, with a focus on increasing competitiveness in the tourism industry. This study uses a qualitative approach. Data collection techniques through observation and interviews. The results show that the hotel offers two menu options (western and Indonesian) to meet different tastes, this also creates operational complexity. In addition, the hotel's reliance on social media marketing, although effective, needs to be expanded with offline strategies such as establishing partnerships with local travel agents. Therefore, Renjana Beach House can improve guest satisfaction and operational efficiency by highlighting local cuisine, implementing an automated booking system, and strengthening collaboration with travel agents and influencers, thereby helping the hotel improve its overall competitiveness and service quality.